2014
DOI: 10.1159/000362141
|View full text |Cite
|
Sign up to set email alerts
|

Pure Trisomy 2p Syndrome in Two Siblings with an Unbalanced Translocation and Minimal Terminal 12q Monosomy Characterized by High-Density Microarray

Abstract: Pure partial trisomy 2p patients have rarely been reported. Oligonucleotide array analysis has proved to be important for examining 2p rearrangements to delineate the involved segment and to rule out additional imbalances modifying the phenotype. Here, we report 2 siblings with an unbalanced translocation that led to a partial trisomy 2p (p22.3pter) and a terminal deletion of 12q (q24.33qter). This finding was characterized by the molecular karyotyping of both siblings. The 12q loss spanned approximately 300 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Growth and psychomotor retardation, microcephaly, prominent forehead, hypertelorism, epicanthal folds, ptosis, strabismus, myopia, low-set ears, flat nasal bridge, narrow high palate, micrognathia, sternal abnormalities, kyphoscoliosis, congenital heart disease, genital hypoplasia, long fingers and toes, hypotonia, and horseshoe kidney have been reported with this duplication [6,7]; however, the clinical variability is considerable. To date, no correlation between the size of the duplication and the severity of the phenotype has been found [6].…”
Section: Introductionmentioning
confidence: 99%
“…Growth and psychomotor retardation, microcephaly, prominent forehead, hypertelorism, epicanthal folds, ptosis, strabismus, myopia, low-set ears, flat nasal bridge, narrow high palate, micrognathia, sternal abnormalities, kyphoscoliosis, congenital heart disease, genital hypoplasia, long fingers and toes, hypotonia, and horseshoe kidney have been reported with this duplication [6,7]; however, the clinical variability is considerable. To date, no correlation between the size of the duplication and the severity of the phenotype has been found [6].…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive review of the literature revealed ten cases presenting with partial trisomy 2p, including our region of interest (Table ) [Stoll et al, ; Fineman et al, ; Wakita et al, ; Engels et al, ; Al‐Saffar et al, ; Aviram‐Goldring et al, ; Ishikawa et al, ; Martinez‐Juarez et al, ]. Interestingly, our patient had the smallest region of 2p duplication among these ten cases and was the only one to exhibit triplication (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…The aberrant region (2p25.3–p25.2) was 6.5 Mb in length, consisting of a duplication of the distal 3.0 Mb and a triplication of the proximal 3.5 Mb. We compare our patient's phenotype to ten previously published patients with isolated terminal duplication 2p, and elaborate on the diagnosis of CHARGE in the context of atypical genetic findings [Stoll et al, ; Fineman et al, ; Wakita et al, ; Engels et al, ; Al‐Saffar et al, ; Aviram‐Goldring et al, ; Ishikawa et al, ; Martinez‐Juarez et al, ].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Pure partial trisomies 2p have been described more rarely and could result from chromosomal duplications or unbalanced translocations involving the short arms of acrocentric chromosomes. About 15 cases have been reported postnatally [Yunis et al, 1979;Parruti et al, 1989;Mégarbané et al, 1997;Kubo et al, 1999;Roggenbuck et al, 2001;Kochilas et al, 2008;Blassnig-Ezeh et al, 2013;Martinez-Juarez et al, 2014;Sperry et al, 2016] and 4 cases prenatally [Siffroi et al, 1994;Aviram-Goldring et al, 2000, cases 2 and 3;Thangavelu et al, 2004, case 1]. Prenatal findings were recorded between 9 and 32 WG and included anencephaly [Thangavelu et al, 2004], intrauterine growth retardation, small stomach, aortic coarctation [Siffroi et al, 1994], and isolated nuchal translucency [Aviram-Goldring et al, 2000] ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%